2021
DOI: 10.3389/fcomp.2021.690389
|View full text |Cite
|
Sign up to set email alerts
|

Is Fun For Wellness Engaging? Evaluation of User Experience of an Online Intervention to Promote Well-Being and Physical Activity

Abstract: Online well-being interventions demonstrate great promise in terms of both engagement and outcomes. Fun For Wellness (FFW) is a novel online intervention grounded in self-efficacy theory and intended to improve multidimensional well-being and physical activity through multi-modal methods. These strategies include capability-enhancing opportunities, learning experiences such as games, video vignettes, and self-assessments. RCT studies have suggested that FFW is efficacious in improving subjective and domain-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…In relation to the context of leisure and amusement, the studies of [29,62,66,69] considered that enjoyment favors good mental health, and, as stated by [76], assumed that the effect was therefore promoting the practice of physical activity through the game on cell phones. But, it is also crucial for professionals to advise their gamified practice in educational establishments [76,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the context of leisure and amusement, the studies of [29,62,66,69] considered that enjoyment favors good mental health, and, as stated by [76], assumed that the effect was therefore promoting the practice of physical activity through the game on cell phones. But, it is also crucial for professionals to advise their gamified practice in educational establishments [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…A sedentary lifestyle is also a cause of early mortality [27], which is why the new global action plan on physical activity has established the goal of reducing physical inactivity by 10% in 2025 and 15% by 2030 [28]. Thus, the need arises to consider gamified physical activity as a possible solution, due to its potential motivational and positive effects on well-being, enjoyment, happiness, and fun [29].…”
Section: Mental Health Implicationsmentioning
confidence: 99%
“…Engagement behavior in the PAS intervention will be assessed at W2 by logging the number of post-introductory challenges completed by PAS participants from the PAS website. Subjective experience in the PAS intervention will be assessed by PAS participants at W2 with a modified questionnaire used in previous research [ 56 ]. The 16-item intervention acceptability questionnaire consists of a mix of 15 quantitative items with Likert-scale (i.e., 0 = strongly disagree to 4 = strongly agree) and one open-ended qualitative item.…”
Section: Methodsmentioning
confidence: 99%
“…The self-efficacy to engage data have not been reported in any previous publications. The engagement data were reported in previous publications to describe engagement with the FFW intervention ( 14 17 ). For example, objective data (i.e., task completion) and subjective data (i.e., user experience) indicated that many (but not all) participants moderately engaged with and enjoyed the FFW intervention ( 17 ).…”
Section: Methodsmentioning
confidence: 99%